Prevalência e persistência de enterobactérias isolados na biodigestão anaeróbia de dejetos bovinos – risco sanitário do biofertilizante - Menezes, Kássia Vidal (2023)
The prevalence of antimicrobial resistance observed among pathogens, as well as populations of ubiquitous bacteria, has placed livestock systems in the center of attention, therefore assessing the health safety of residues from anaerobic digestion is essential for the application of biofertilizer in the field. The objective of this study was to characterize 488 suggestive isolates of Escherichia coli from the effluent and biofertilizer of bovine manure, collected in an anaerobic biodigester operated at room temperature in the summer and winter periods of 2022, in terms of tolerance to biocides, antimicrobial resistance and associated with these characteristics, the ability to form biofilms. Physical-chemical analyzes showed a reduction of more than 50% in the total solids content of the samples after the anaerobic digestion process. The biocide and antimicrobial susceptibility test was determined using the disk diffusion method on plates and the biofilm capacity through the 0.1% crystal violet staining method on polystyrene plates. Among the effluent isolates (n=260), regardless of seasonality, 8.84% (n=23) were resistant to 10% polyvidone iodine, 11.53% (n=30) to 2% sodium hypochlorite, not being resistance to 2% chlorhexidine was observed. Among the biofertilizer isolates (n=225), 16% (n=36) were resistant to polyvidone-iodine, 10.66% (n=24) to sodium hypochlorite and 0.44% (n=1) to chlorhexidine, regardless of seasonality. Levofloxacin was the most effective drug for all isolates regardless of seasonal variation, with susceptibility rates greater than 91%, followed by meropenem with 90%. Resistance was often encountered in response to tetracycline drugs with resistance rates up to 19%, followed by gentamicin at 17.24%. 25 isolates were considered multiresistant (MDR), in which, 16 (64%) were resistant to three drugs, 7 (28%) to four, 2 (8%) to five drugs tested. There was evidence of biofilm formation capacity of practically all isolates 98.12% (n=479). Isolated from the effluent and biofertilizer in the summer period showed the same in vitro biofilm formation ability, and a significant percentage of 65.31% was attributed to moderate and very adherent 11 adherence of the bacteria isolated from the biofertilizer in the winter period. A positive correlation was observed between MDR and greater biofilm formation capacity both in the effluent (OR 10.25) and in the biofertilizer (OR 1.55) samples, however, a negative correlation was observed for the MDR and the increase in tolerance to the biocides. These results reveal that rigorous monitoring is needed regarding virulence and antimicrobial resistance from by-products of animal production and related products, such as biofertilizers, which can pose potential risks to public health.